Smart heuristics for individuals, teams, and organizations - GIGERENZER, Gerd (Institutional Knowledge at Singapore Management University, 2022)
Heuristics are fast, frugal, and accurate strategies that enable rather than limit decision making under uncertainty. Uncertainty, as opposed to calculable risk, is characteristic of most organizational contexts. We review existing research and offer a descriptive and prescriptive theoretical framework to integrate the current patchwork of heuristics scattered across various areas of organizational studies. Research on the adaptive toolbox is descriptive, identifying the repertoire of heuristics on which individuals, teams, and organizations rely. Research on ecological rationality is prescriptive, specifying the conditions under which a given heuristic performs well, that is, when it is smart. Our review finds a relatively small but rapidly developing field. We identify promising future research directions, including research on how culture shapes the use of heuristics and how heuristics shape organizational culture. We also outline an educational program for managers and leaders that follows the general approach of “Don't avoid heuristics—learn how to use them.”